2021
DOI: 10.1016/j.biochi.2021.05.017
|View full text |Cite
|
Sign up to set email alerts
|

What do secreted phospholipases A2 have to offer in combat against different viruses up to SARS-CoV-2?

Abstract: Secreted phospholipases A 2 (sPLA 2 s) form a widespread group of structurally-related enzymes that catalyse the hydrolysis of the sn -2 ester bond of glycerophospholipids to produce free fatty acids and lysophospholipids. In humans, nine catalytically active and two inactive sPLA 2 proteins have been identified. These enzymes play diverse biological roles, including host defence against bacteria, parasites and viruses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…During early stages of coronavirus infection, PLA2s are activated as evidenced by increased cellular levels of lysophospholipids and FFAs such as LA, arachidonic acid, oleic acid, and palmitoleic acid in both SARS-CoV-2-infected cell cultures and SARS-CoV-2-infected patients (16,(24)(25)(26). A central regulator of lipidome remodeling during β-CoV infection is cPLA2.…”
Section: La Treatment Of Sars-cov-2-infected Cells Suppresses Viral R...mentioning
confidence: 99%
“…During early stages of coronavirus infection, PLA2s are activated as evidenced by increased cellular levels of lysophospholipids and FFAs such as LA, arachidonic acid, oleic acid, and palmitoleic acid in both SARS-CoV-2-infected cell cultures and SARS-CoV-2-infected patients (16,(24)(25)(26). A central regulator of lipidome remodeling during β-CoV infection is cPLA2.…”
Section: La Treatment Of Sars-cov-2-infected Cells Suppresses Viral R...mentioning
confidence: 99%
“…sPLA2 levels are correlated to clinical severity in the COVID-19 population, including a pediatric subset. 17,19,110114 Even though they represent only a fraction of the total severe COVID-19 cases, pediatric COVID-19 has become a major public health issue. Diorio et al 115 demonstrated an elevation in cytokine profiles associated with multisystem inflammatory syndrome in children (MIS-C), in children infected with COVID-19, suggesting that early identification of inflammatory factors like sPLA2 is valuable to monitor disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…During early stages of coronavirus infection, phospholipase A2s (PLA2s) are activated as evidenced by increased cellular levels of lysophospholipids and FFAs such as LA, arachidonic acid, oleic acid and palmitoleic acid in both SARS-CoV-2 infected cell cultures and SARS-CoV-2 infected patients (16, [24][25][26]. A central regulator of lipidome remodeling during -CoV infection is cytoplasmic PLA2 (cPLA2).…”
mentioning
confidence: 99%